2013
DOI: 10.5937/fizkul1301024d
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the motivational intervention on students' motor abilities

Abstract: УТИЦАЈ ЕКСПЕРИМЕНТАЛНОГ ПРОГРАМА МОТИВАЦИЈЕ НА МОТОРИЧКЕ СПОСОБНОСТИ УЧЕНИКА СажетакПредмет проучавања овог рада била је мотивација ученика старијих разреда основне школе у настави физичког васпитања. Циљ истраживања био је да се у пракси тестира оригинални програм мотивације ученика за наставу физичког васпитања и види да ли је он допринео побољшању моторичких способности ученика и смањењу изостанака са наставе. Узорак испитаника чинила су по два одељења шестог, седмог и осмог разреда основне школе у експерим… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…In addition, the review aimed to identify whether there was a link between certain teacher training characteristics and FMS and/or PA improvement. Approximately one-quarter of the studies included in this review did not report on any aspect of the teacher training conducted, despite teachers facilitating the school-based FMS and/or PA intervention [48,49,52,53,63,64,67,72,77]. Therefore, for these studies it is not possible to determine the extent of the influence that teacher training had on intervention outcomes.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…In addition, the review aimed to identify whether there was a link between certain teacher training characteristics and FMS and/or PA improvement. Approximately one-quarter of the studies included in this review did not report on any aspect of the teacher training conducted, despite teachers facilitating the school-based FMS and/or PA intervention [48,49,52,53,63,64,67,72,77]. Therefore, for these studies it is not possible to determine the extent of the influence that teacher training had on intervention outcomes.…”
Section: Discussionmentioning
confidence: 77%
“…Teacher training was not reported in almost a quarter of the studies (23 %, 9/39) [48,49,52,53,63,64,67,72,77]. In one of these studies, it was reported that the teachers had received training prior to the intervention, yet no further teacher training detail was provided in the paper [49].…”
Section: Teacher Training Characteristicsmentioning
confidence: 81%
See 3 more Smart Citations